Differences between gender and population groups, motivational variables and healthy lifestyles - Leyton, Marta (2019)
The objective of our study was to analyse the difference between genders in the population groups under and over 40 years old, in relation to healthy lifestyles variables such as the intention to be physically active, balanced diet, tobacco, rest, as well as motivational variables related to the practice of physical activity. The sample consisted of 858 subjects, aged between 18 and 77 years old (41.62 ± 13.30). The instruments used for collection data were the Behavioural Regulation Exercise Questionnaire, for the Intrinsic Motivation measurement, the Intentionality to be Physically Active Measurement Scale, for the intention of future practice measurement, and the Healthy Lifestyles Questionnaire, for the tobacco consumption, rest, balanced diet and respect to the meal schedule variables measurement. The results determined that men have more intention to be physically active, higher more self-determined motivation and greater balanced diet, than women, both in the group under 40 years, and in the group over 40 years It was concluded that men have higher means in variables related to lifestyle, in relation to women.